2004
DOI: 10.1160/th03-08-0548
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombinase enhancement through quantitative and qualitative changes affecting very low density lipoprotein in complex with C-reactive protein

Abstract: The biphasic waveform that can predict for disseminated intravascular coagulation (DIC) is due to the formation of a calcium-dependent complex between C reactive protein (CRP) and very low density lipoprotein (VLDL). As thrombin generation is pivotal to DIC, this aspect has been specifically investigated and the VLDL component has been found to increase prothrombinase activity via both quantitative and qualitative changes. The specific prothrombinase activity of VLDL from patients manifesting the biphasic wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…The very low density lipoprotein components from patients with BPW have been found to increase prothrombinase activity (29). The BPW is a transient phenomenon, lasting 2-3 days and preceding the diagnosis of overt disseminated intravascular coagulation by Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…The very low density lipoprotein components from patients with BPW have been found to increase prothrombinase activity (29). The BPW is a transient phenomenon, lasting 2-3 days and preceding the diagnosis of overt disseminated intravascular coagulation by Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown here that the CRP was increased in the patients with high DIC scores. CRP was highly elevated in the DIC patients having a biphasic transmittance waveform, and thrombin generation could be promoted by the CRP-very low density lipoprotein complex [14]. Even though the CRP level alone does not predict DIC, the CRP level, which was correlated with DIC score, may have a physiological role in the active thrombin generation of DIC.…”
Section: Discussionmentioning
confidence: 99%
“…ANXA5 is a member of the annexin family of calcium-dependent phospholipid-binding proteins (10). In addition, a previous study by Dennis et al (11) reported that ANXA5 may affect triglyceride metabolism. These results suggested that an association between ANXA5 and lipid metabolism may be an important aspect of obesity.…”
Section: Introductionmentioning
confidence: 95%